FOREIGN UNIVERSITIES IN QATAR: A CRITICAL REVIEW OF POLICY AND SUSTAINABILITY ISSUES - Fethi B Jomaa AHMED (Challenges of the Knowledge Society, 2019)
Qatar is transitioning toward knowledge society and aims at becoming a hub for international education. The Permanent Constitution and the Nation Vision 2030 of Qatar explicitly refer to the role of government in promoting sound education as making it the prime driver of human, social and economic development. The government has invested 3.5% of its GDP in education. Since 1998, Qatar has succeeded in contracting 11 International foreign universities to open branches in Qatar. These International Branch Campuses (IBCs) include Texas A&M University, Weill Cornell Medical College, Georgetown University, University College London and University of Calgary. The IBCs offer a range of specializations and degree programs such as medicine, engineering, foreign affairs, journalism, and tourism. Qatar spends more than US$400 million annually on the six US branch campuses only excluding construction expenses. Hence, this study attempts to examine Qatar’s policy on the IBCs and investigate its sustainability. The author focuses on discussing critical policy issues including English as language of instruction, mixed-gender education, and the ‘glocalization’ of the IBCs. Moreover, he addresses sustainability issues related to the IBCs such as the political will, diversification of the economy, and the contribution of the IBCs to Qatar’s society. Ultimately, the author is enthusiastic that this library-based, theoretical and critical study would provoke more scholarly debates on Qatar’s unique model of hosting foreign universities campuses.